New Black Queer Cinema - Wallenberg, Louise (New Queer Cinema: A Critical Reader, 2004)
In 1989, three years before the New Queer Wave was even invented or discovered, two very different yet interconnected films were produced on either side of the Atlantic. Both soon became critically successful and both would win a number of prizes at different international film festivals and venues. In retrospect, these two films have come to constitute the very incitement to the Wave. British filmmaker Isaac Julien’s Looking for Langston premiered in early 1989 and American filmmaker Marlon Riggs’s Tongues Untied premiered later that same year, the latter including a still photo from the former so as to pay homage
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé